Evaluating the Impact of an Educational Program Based on the Health Belief Model in Promoting Preventive Behaviors for Nosocomial Infections among Nurses - Faiz Hadroos Alhazimi, Mohammed Hadroos Alhazimi, Naifah Lafi Ayed Almajdi, Eessa Obaidallah Ali Alrasheedi, Mousa Obaidallah Ali Alrashdi, Meznah Ali Albazaly (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
This study aims to assess the impact of an educational program based on the Health Belief Model (HBM) in promoting preventive behaviors for nosocomial infections among nursesMethods: A study involving 120 nurses working in a hospitalwas conducted. The nurses were divided into two groups: the intervention group (n=60) received the educational program based on HBM, while the control group (n=60) did not receive it. A questionnaire was used to measure HBM constructs (knowledge, perceived susceptibility, perceived severity, perceived benefits, perceived barriers, self-efficacy, performance, and cues to action) at baseline, immediately after the intervention, and four months post-intervention.Results: The intervention group showed significant improvements in knowledge, perceived susceptibility, perceived severity, perceived benefits, self-efficacy, cues to action, and performance immediately and four months after the intervention compared to the control group.Conclusion: This study demonstrates the effectiveness of the educational program based on HBM in promoting preventive behaviors for nosocomial infections among nurses . The HBM can serve as a valuable framework for designing and implementing similar educational interventions to prevent nosocomial infections.